Combate del gusano cogollero del maíz (Laphigma frugiperda S. and A.) por medio de insecticidas en Nicaragua - Estrada, Francisco A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
At the Agricultural Experiment Station of La Calera, near Managua, experiments were conducted in order to find out which chemicals could be used to control several covn insect of special importance as the fall army worm (Laphigma frugiperda Smith and Abbott) which reduces the crop considerably if no insecticides are used Several products were used, but methyl parathion proved to be the most effective, because of its rapid action; its application is recommended for areas of frequent vains DDT and dieldrin have a slower action but have a longer residual effect and can be used under dry weather conditions Dieldrin might injure young plants when used in higher con-centrations than recommended.